2022
DOI: 10.1007/s10668-022-02780-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors driving CO2 emissions: the role of energy transition and brain drain

Abstract: This investigation explored the impacts of energy transition and brain drain on carbon dioxide (CO2) emissions. A panel of seventy-five countries from 2006 to 2020 and the panel quantile regression were used to realize this investigation. The empirical results from the panel quantile regression indicated that the brain drain, trade openness, and economic growth increase CO2 emissions per capita. At the same time, the energy transition, energy efficiency, and urbanization mitigate the environmental degradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 115 publications
(133 reference statements)
0
8
0
Order By: Relevance
“…In contrast, urbanization (% of the total population), environmental patents, and environmental tax as a percentage of total tax reduce CO 2 gas emissions. Kazemzadeh et al (2023) investigate the nexus between economic growth, institutional quality, urbanization and energy consumption on carbon emissions. The model results shows that model allows for exploring sufficient conditions and identifying the optimal combination of variables that increase or decrease the ecological footprint.…”
Section: Governance and Environmental Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, urbanization (% of the total population), environmental patents, and environmental tax as a percentage of total tax reduce CO 2 gas emissions. Kazemzadeh et al (2023) investigate the nexus between economic growth, institutional quality, urbanization and energy consumption on carbon emissions. The model results shows that model allows for exploring sufficient conditions and identifying the optimal combination of variables that increase or decrease the ecological footprint.…”
Section: Governance and Environmental Qualitymentioning
confidence: 99%
“…Using ARDL model, the findings shows that energy consumption and industrialization raise carbon emissions in Russia. Kazemzadeh, (2022b) explore the effect of energy transition on carbon emissions in five countries from 2006 to 2020 using panel quantile regression. The findings shows that brain drain, trade openness, and economic growth increase CO 2 emissions per capita.…”
Section: Economic Growth Energy Consumption and Carbon Emissionsmentioning
confidence: 99%
“…Following Kazemzadeh et al (2022) and Zhongming et al ( 2019), we used the Dumitrescu and Hurlin (2012) causality test to explore the causal paths amidst the series. This approach was used because it accounts for heterogeneity and CD in panel units.…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…Progress in technological change like renewable energy technology adoption is not likely to occur in a smooth pattern. 28 This pattern includes drivers and barriers which may lead to subsequent technological breakthroughs or slow deployment. 22 On the constraints to renewable electric power deployment, Foster et al 29 found that the cost of fossil fuel power generation responds to the large-scale penetration of renewables making the renewable energy transition slower or more costly than anticipated.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other macroeconomic variables, such as GDP per capita used to capture the level of development, FDI, human capital, and public policy factors, are found to be other factors that account for the renewable electricity penetration. 25,[26][27][28][29][30][31][32][33][34][35] Thus, in addition to macroeconomic variables, this study accounted for the role of national renewable energy policy legislation on renewable electricity adoption in SSA.…”
Section: Literature Reviewmentioning
confidence: 99%